Demographic Status Of Midimaavu In Chikmagalur District, Central Western Ghats, India - Chaithra, G. N.; Tambat, B.; Prasanna, N. S.; Srinivas, C. (Indian Forester, 2014)
Midimaavu is one of the mango varieties known for making pickles. Unlike mango slices, entire tender mango is used for pickling and the pickles can be stored up to 3 to 4 years without any preservatives. However, it has been reported that most Midimaavu varieties are restricted to certain geographical locations in central Western Ghats, India and are harvested mostly from the forests. Thus they are considered as an important non-timber forest produce (NTFP) in the areas. We assessed the demographic profile of Midimaavu in Chikmagalur district, central Western Ghats, Karnataka. As per results, the typical reverse "J" shaped curve was not observed in many populations. Further the density and regeneration per adult analysis indicated populations suffer due to poor regeneration and subsequent sapling survival. The present study reveals that midimaavu is suffering from low recruitment and survival, thus there is an urgent need for conservation action.